Pengaruh Volume Media Tanam Terhadap Pertumbuhan Dan Hasil Edamame (Glycine max (l) Merril) Dalam Polybag - Christoforus Dandy Driartaka; Dina Rotua Valentina Banjarnahor (Universitas Tidar, 2026)
Limited availability of fertile land has led to the adoption of a polybag cultivation system for edamame soybeans (Glycine max (L.) Merr.), in which plant growth is influenced by the volume of growing medium. This study aimed to examine the effect of varying growing medium volumes on the growth and yield of the Biomax 1 edamame variety and to determine the optimal growing medium volume. The study was conducted from August to October 2025 at the Kartini Farm using a non-factorial Randomized Block Design (RBD) with five growing medium volume treatments—4 L, 6 L, 8 L, 10 L, and 12 L—each replicated five times. Data were analyzed using ANOVA at the 5% significance level, followed by the Honest Significant Differences (HSD) test. The results showed that growing medium volume had a significant effect on most growth and yield parameters, except for plant height and seed protein content. A growing medium volume of 12 L yielded the best results and is recommended to increase edamame productivity in the polybag cultivation system.